Efficient metal-free organic room temperature phosphors - Nidhankar, Aakash D.; Goudappagouda; Wakchaure, Vivek C.; Babu, Sukumaran Santhosh (Chemical Science, 2021)
An innovative transformation of organic luminescent materials in recent years has realised the exciting research area of ultralong room-temperature phosphorescence. Here the credit for the advancements goes to the rational design of new organic phosphors. The continuous effort in the area has yielded wide varieties of metal-free organic systems capable of extending the lifetime to several seconds under ambient conditions with high quantum yield and attractive afterglow properties. The various strategies adopted in the past decade to manipulate the fate of triplet excitons suggest a bright future for this class of materials. To analyze the underlying processes in detail, we have chosen high performing organic triplet emitters that utilized the best possible ways to achieve a lifetime above one second along with impressive quantum yield and afterglow properties. Such a case study describing different classes of metal-free organic phosphors and strategies adopted for the efficient management of triplet excitons will stimulate the development of better candidates for futuristic applications. This Perspective discusses the phosphorescence features of single- and multi-component crystalline assemblies, host-guest assemblies, polymers, and polymer-based systems under various classes of molecules. The various applications of the organic phosphors, along with future perspectives, are also highlighted.